Study of river shifting of Kodku Khola in Kathmandu Valley using remotely sensed data - Pathak, D; Gajurel, AP; Shrestha, GB (Journal of Nepal Geological Society, 2008)
Kodku Khola (river) is north flowing tributary of the Manahara River and is located in the southern part of the Kathmandu Valley. The catchment area of the Kodku Khola is around 34 km2 and the head ward area is occupied by steep mountainous terrain and composed of hard rocks (e.g. limestone, sandstone, shale etc.). The Kodku Khola flows through the semi-consolidated fluvio-lacustrine sediments of the Kathmandu Basin fill deposits before merging to Manahara River. In this study, the natural river shifting as well as shifting caused by the human interferences and their environmental consequences is studied. The temporal remote sensing data (aerial photo and satellite images) and field survey has revealed that the river shifting is intense in the lower reaches of the river. Two basic factors are mainly responsible for the shifting of rivers: manmade river shifting that is induced due to intense population concentration in the Kathmandu valley and the river shifting caused by natural river processes. The areas in the lower reaches of the river are densely populated. Large number of buildings and infra-structures are under construction near by the river sides. The Kodku Khola changes its course ranging from 19-60 m at Balkumari, 16-98 m at Gwarko (near Cinema Hall), 25-82 m between Gwarko and Hattiban as well as around the housing complex at Harisiddhi. Near Balkumari, there has been significant course change of river that is resulted both from the man-made and natural causes during the last 19 years (between 1988 and 2007). Three different channels (two traces of natural and one man-made active channel) of the Kodku Khola are observed near Gwarku Cinema Hall. It is a good example showing how the meandered river is shifting its course naturally and also it is confined to very narrow channel due to engineering constructions around the river banks. The private housing company has diverted the Kodku Khola channel by constructing bank protection wall between Gwarko and Hattiban. Similar is the case in Harisiddhi. The emerging housing complexes are the prime reasons for the artificial river shifting of Kodku Khola. When the river is confined to narrow channel, both the upstream and downstream areas are affected. During the field observation, it has been observed that there has been quite significant flooding effects and river aggradation. Further, river breaching within the confined channel has also caused inundation at the agricultural areas as well as settlements around the banks of the river, the downstream area being at high risk. Journal of Nepal Geological Society, 2007, Vol. 36 (Sp. Issue) p.28